Influence of Hyperglycemia During Different Phases of Ischemic Preconditioning on Cardioprotection—A Focus on Apoptosis and Aggregation of Granulocytes. Issue 5 (May 2020) - Goergens, Jessica I.; Heinen, Nicole M.; Zoller, Jan; Preckel, Benedikt; Bauer, Inge; Huhn, Ragnar; Ebel, Dirk; Raupach, Annika
ABSTRACT: Background: Ischemic preconditioning (IPC) protects the myocardium against ischemia/reperfusion injury. Evidence suggests that hyperglycemia inhibits IPC-induced cardioprotection. The effects of hyperglycemia initiated during different phases of IPC on myocardial injury were characterized with emphasis on apoptosis and aggregation of polymorphonuclear granulocytes (PMN). Methods: Male Wistar rats were subjected to 35 min of myocardial ischemia and 2 h of reperfusion. Control animals were not further treated. IPC was induced by three cycles of 3 min ischemia and 5 min of reperfusion before major ischemia. Hyperglycemia (blood glucose more than 22.2 mmol/L) was induced by glucose administration with or without IPC during different phases (trigger- (before ischemia), mediator- (during ischemia), early reperfusion-phase). One additional group received an anti-PMN-antibody before ischemia. Infarct size was quantified by triphenyltetrazolium chloride staining. Cytochrome C release and B-cell lymphoma two (Bcl-2) expression were assessed by western blot analysis. Poly-ADP-Ribose staining and PMN accumulation were quantified with immunohistochemistry and histochemistry. Results: IPC reduced infarct size compared with control. Hyperglycemia completely abolished IPC-induced cardioprotection independent of the time point of initiation. Hyperglycemia before and during major ischemia but without IPC also slightly reduced infarct size. IPC reduced the accumulation of PMNs. This effect was reversed by hyperglycemia during trigger- and mediator-phase but not by hyperglycemia during reperfusion. Hyperglycemia alone had no effect on PMN accumulation. In all treatment groups, signs of myocardial apoptosis were reduced compared with control. IPC alone, combined with hyperglycemia and anti-PMN treatment, reduced apoptosis by a Bcl-2-associated mechanism. Hyperglycemia alone reduced apoptosis by a Bcl-2-independent pathway. Conclusion: Hyperglycemia inhibits IPC-induced cardioprotection independent of its onset. Furthermore, hyperglycemia prevents apoptosis and IPC-induced reduction of PMN aggregation.